Integration of EPC Contracts in Enhancing Energy Efficiency in Sustainable Development Projects - Sugiarto Amalia Rizka; Khaerani Fatma Nur; Winarsih Neneng; Masyita Nurani; Abdi Grisela Nurinda; Suryadi Cahya; Purnama Dicki Dian; Amal Bahar (E3S Web of Conferences)
The integration of Engineering, Procurement, and Construction (EPC) contracts offers a comprehensive approach to enhancing energy efficiency in sustainable development projects. By combining design, procurement, and construction into a single streamlined process, EPC contracts have the potential to optimize resource use and support the adoption of energy-saving technologies. This study investigates the role of EPC contracts in achieving energy efficiency objectives through case studies of sustainable projects, including renewable energy facilities, green buildings, and industrial developments. The findings indicate that EPC contracts facilitate the implementation of energy-efficient solutions by ensuring better coordination, optimized resource allocation, and adherence to project timelines. Moreover, the framework supports significant reductions in energy consumption and carbon emissions while maintaining cost-effectiveness. Key factors contributing to these outcomes include integrated planning, the use of advanced technologies, and efficient project execution practices. This research concludes that EPC contracts play a vital role in promoting energy efficiency in sustainable development projects. The study provides recommendations for developers, contractors, and policymakers to leverage EPC frameworks effectively, contributing to global sustainability goals.